1P53 over expression in skin lesions: An immunohistochemical study - Omer, Salah A.; Qasim, Yusra Abdulkhaliq; Omar, Jawhar Taher (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objective: Immunohistochemistry is the application of immunologic principles and techniques to demonstrate molecules in cells and tissues. Gene p53 is a tumor-suppressor gene. The product of this gene is a nuclear protein thought to be involved in the control of the cell cycle, apoptosis, and the maintenance of genomic stability. Gene p53 is the most frequently mutated tumor suppressor gene found in human cancer. The aim of this study was to investigate p53 protein over expression in skin cancer and compare it with benign skin lesion. Methods: A retrospective study was conducted on paraffin block from skin biopsy of 36 patients with various skin lesions; eight benign cases and 28 malignant cases. The sample of patients was collected from the Pathology Laboratory in Rizgary Teaching Hospital in Erbil, Kurdistan region, Iraq from December 2011 to December 2012. The age of the patients ranged from 34 to 80 years. The p53 protein over expression was investigated by immunohistochemical staining. Sample sections were stained and scored. Results: Nineteen out of 28 (76.8%) skin cancer showed over expression of p53 gene compared with benign skin lesion and there was a statistically significant difference. There was statistical significant difference in relation to the age group of patients with various skin cancers which was higher in patient above 40 years. Conclusion: Increased expression of p53 a nuclear protein can be detected in human skin cancer compared with benign skin lesion and it may play an important role in pathogenesis of many types of skin cancers.